Issues of Political Dynasties and National Protest Movements in Indonesia: Appraisal and Critical Discourse Analysis Perspectives in Editorials - Fahmi Gunawan; Arbain; Abd. Rahman Zain; Sakut Anshori (Script Journal: Journal of Linguistics and English Teaching, 2026)
Abstract Background: Political dynasties represent an enduring challenge to democratic consolidation in Indonesia. However, the role of media discourse in shaping public perceptions of dynastic power remains under-explored, particularly regarding how editorial narratives frame dynastic politics and subsequent protest movements. Drawing upon Fairclough’s Critical Discourse Analysis (CDA) and Martin & White’s Appraisal Theory, this study conceptualizes editorials as discursive spaces where political legitimacy is systematically constructed and negotiated. Methodology: This study analyzes three editorials published in The Jakarta Post in 2024: “Breaking A Dynastic Habit” (July 5), “People Have Spoken” (August 26), and “Thank You for Speaking Up” (August 29). These texts address political dynasties and protests triggered by the controversial revision of minimum age requirements for regional head candidates. This media outlet was selected for its prominent national standing, its English-speaking readership, and its influential role in shaping elite public discourse. The analysis integrates Appraisal resources (Attitude, Engagement, and Graduation) with Fairclough’s three-dimensional CDA framework. Attitude is employed to identify evaluative stances toward political actors; Engagement to trace the management of dialogic voices; and Graduation to assess the intensity of political event representations. Findings: The results reveal a patterned evaluative asymmetry: political dynasties are represented through negative moral judgments and procedural critiques, whereas protest movements are framed as rational, ethically grounded civic responses. Intensification resources contribute to framing political dynamics as urgent or significant, while heteroglossic strategies allow for the inclusion of diverse voices while maintaining a specific evaluative position. These linguistic patterns indicate a systematic inclination to steer readers toward particular interpretations of political legitimacy. Conclusion: Editorial discourse does more than report events; it constructs interpretative frameworks that influence the conceptualization of legitimacy and dissensus within the context of contemporary democracy. Originality: This research extends the application of Appraisal Theory in ideological discourse analysis by demonstrating how evaluative language operates systematically to represent political actors and processes in a volatile democratic landscape.